The Prospect and Legal Issues of Income Tax in the Nigerian Metaverse - Aidonojie, Paul Atagamen; Eregbuonye, Obieshi; Majekodunmi, Afolabi Toyin; Inagbor, Michael E. (TRUNOJOYO LAW REVIEW, 2024)
The Metaverse, a virtual space encompassing augmented reality, virtual reality, and the internet, has witnessed rapid growth, giving rise to complex economic activities. However, it suffices to state that despite the relevance of the metaverse concept in the global terrain, Nigeria, like many nations, could face the challenge of adapting its tax laws to the unique characteristics of the Metaverse. Given this, this study adopts a hybrid method of study to explore the taxation challenges within the Nigerian Metaverse, evaluating the efficacy of current tax laws and regulations in this evolving digital landscape. In this regard, 352 questionnaires were distributed to legal practitioners residing in Nigeria to ascertain their views concerning the sufficiency and deficiency of the existing tax laws regulating the tax issues in the metaverse. The study's findings reveal significant challenges in existing tax laws, including jurisdictional complexities, defining taxable income in virtual environments, identifying entities subject to taxation, enforcing regulations without physical assets, overcoming technology gaps, and ensuring legislative adaptability to digital advancements. These challenges hinder the growth of the Metaverse industry and pose risks in revenue generation within the metaverse operation in Nigeria. It was therefore concluded that there is an urgent need to adapt tax policies to the unique characteristics of the Metaverse in Nigeria. A balance between innovation and regulatory oversight is crucial for sustainable growth in the virtual economy. In this regard, the study recommended clear definitions and classifications of virtual assets, considering international best practices and collaborating with international bodies to establish a comprehensive and adaptive legal framework for taxing Metaverse activities in Nigeria.